English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-16 11:55:36 · 4 answers · asked by sigmarhoer06 1 in Science & Mathematics Mathematics

4 answers

I assume your x is in the denominator, but the -c is not.

Original equation:
a / (bx) - c = 0

Add c to both sides:
a / (bx) = c

Multiply both sides by bx:
a = cbx

Divide both sides by bc:
a / (bc) = x

x = a / (bc)

2006-11-16 11:59:08 · answer #1 · answered by Puzzling 7 · 0 0

step 1: bring c to other side so we get:
a/bx=c
step 2: time bx with c we get:
a=bxc
then x=a/bc

2006-11-17 12:19:48 · answer #2 · answered by Anonymous · 0 0

X=a/bc

2016-09-13 12:14:50 · answer #3 · answered by Rugazura 1 · 0 0

x =(c*b)/a

2006-11-16 11:57:22 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers